Internalisasi Nilai Keberanian Pada Proses Pembelajaran Untuk Membentuk Karakter Siswa Kelas V SDN 8 Kota Bengkulu - Sari, Epita; Supriatna, Irfan (JURIDIKDAS, 2025)
The value of courage is one of the principles in the Scout Dasadarma. This study aims to describe how teachers internalize the value of courage during learning and how students respond afterward. This qualitative descriptive research involved Scoutmasters, class 5C teachers, and class 5C students. Data were collected through observation, interviews, and documentation, with triangulation and member checks used to ensure credibility. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings show that the class 5C teacher implemented the three stages of value internalization: the Value Transformation Stage, the Value Transaction Stage, and the Value Trans-internalization Stage. The teacher applied character education using exemplary methods, habituation, advice, punishment, and emotional approaches to instill courage. These methods were integrated into the learning process to help shape student character. As a result, students of class 5C demonstrated positive behavioral changes and displayed courageous attitudes following the teacher’s efforts. In conclusion, the process of internalizing the value of courage in students was successfully carried out through structured character education approaches. The consistent application of exemplary behavior, routines, emotional connections, and disciplinary actions contributed to fostering courage in students in a meaningful and observable way.